The impact of minimum wages on wages, work and poverty in Nicaragua - Enrique Alaniz; T. H. Gindling; Katherine Terrell (Institute for the Study of Labor (IZA), 2011)
We use an individual-level panel data set to study the impact of changes in legal minimum wages on a host of labor market outcomes in Nicaragua including: a) wages and employment, b) transitions of workers across jobs (in the covered and uncovered sectors) and employment status (unemployment and out of the labor force), and c) transitions into and out of poverty. We find that changes in the legal minimum wage affect only those workers whose initial wage (before the change in minimum wages) is close to the minimum. For example, increases in the legal minimum wage lead to significant increases in the wages and decreases in employment of private covered sector workers who have wages within 20% of the minimum wage before the change, but have no significant impact on wages in other parts of the distribution. The estimates from the employment transition equations suggest that the decrease in covered private sector employment is due to a combination of layoffs and reductions in hiring. Most workers who lose their jobs in the covered private sector as a result of higher legal minimum wages leave the labor force or go into unpaid family work; a smaller proportion find work in the public sector. Our analysis of the relationship between the minimum wage and household income finds: a) increases in legal minimum wages increase the probability that a poor worker's family will move out of poverty, and b) increases in legal minimum wages are more likely to reduce the incidence of poverty if they impact the head of the household rather than the non-head.
urn:nbn:de:101:1-201105306250
Keywords: J3; O17; 330; minimum wages; employment; poverty